Two new species of the genus Criotettix Bolivar (Orthoptera: Tetrigoidea: Scelimenidae) from Zhejiang, China - Zhang, Ziyang; Liu, Zhixing; Yin, Hong (Zootaxa, 2021)
Two new species of the genus are described from Zhejiang, China in this paper. The new species Criotettix jinningensis sp. nov. is similar to Criotettix strivertexoides Zheng, Wei & Li, 2009, but differs in width of vertex narrower than diameter of eye; pronotum shorter, not reaching the end of hind tibiae; width of fore wing 1.3 times width of mid leg femur and hind wing not reaching the end of pronotum. The new species Criotettix pananensis sp. nov. is similar to Criotettix transpi-noides Zheng, Bai & Xu, 2012, it differs from latter by width of vertex narrower than diameter of eye; pronotum with parallel lateral keels and without a pair short longitudinal keels between shoulders; hind femur without projection in upper keel and hind wing extending over the end of pronotum. The type specimens are deposited in the College of Life Sciences, Hebei University, Baoding, China.